Pengaruh Job Demands dan Job Resources Terhadap Work Engagement Guru - Izzah Ramadhani Astisya; Cholichul Hadi (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2021)
Employees who are engaged in their jobs will be more committed to the organization,are less often absent, and do not intend to leave the organization (Schaufeli, 2012). Teaching is like any other profession that requires work engagement. The factor that is often used to explain its effect on work engagement are job demands and job resources. Every teachers have to deal with job demands at work and requires job resources to support them. The aims of the study is to determine the effect of job demands and job resources on work engagement. This research was conducted on 184 teachers who teach in elementary school, junior and senior high school. Data was collected by using questionnaire forms of a UWES-9 scale and JDRS scale. The data was analyzed by ordinal regression and the result shows that job demands and job resources did not affect work engagement on teacher.